Implementation of Balanced Scorecard in Improving Organizational Performance - Ardenny; Rosalia, Olyvia (Maneggio, 2025)
This study aims to examine the impact of Balanced Scorecard (BSC) implementation on improving organizational performance. The BSC is a strategic management tool that evaluates performance from four perspectives: financial, customer, internal business processes, and learning and growth. Using a quantitative approach with descriptive and verification methods, data were collected through questionnaires distributed to employees and managers in organizations that have formally implemented BSC. The results show that each BSC perspective has a significant positive influence on organizational performance, especially in enhancing financial efficiency, customer satisfaction, internal process optimization, and employee development. However, successful implementation is closely linked to top management commitment, organization-wide understanding of BSC, and adequate training resources. This study provides practical insights for organizations seeking to improve performance through structured and sustainable BSC application.